Cyber warfare and the laws of war - Dinniss, Heather Harrison (Cambridge studies in international and comparative law, 2012)
The information revolution has transformed both modern societies and the way in which they conduct warfare. This book analyses the status of computer network attacks in international law and examines their treatment under the laws of armed conflict.